The Submarine Boundaries of Mount Etna’s Unstable Southeastern Flank - Urlaub, Morelia; Geersen, Jacob; Petersen, Florian; Gross, Felix; Bonforte, Alessandro; Krastel, Sebastian; Kopp, Heidrun (Frontiers in Earth Science, 2022)
Coastal and ocean island volcanoes are renowned for having unstable flanks. This can lead to flank deformation on a variety of temporal and spatial scales ranging from slow creep to catastrophic sector collapse. A large section of these unstable flanks is often below sea level, where information on the volcano-tectonic structure and ground deformation is limited. Consequently, kinematic models that attempt to explain measured ground deformation onshore associated with flank instability are poorly constrained in the offshore area. Here, we attempt to determine the locations and the morpho-tectonic structures of the boundaries of the submerged unstable southeastern flank of Mount Etna (Italy). The integration of new marine data (bathymetry, microbathymetry, offshore seismicity, reflection seismic lines) and published marine data (bathymetry, seafloor geodesy, reflection seismic lines) allows identifying the lineament north of Catania Canyon as the southern lateral boundary with a high level of confidence. The northern and the distal (seaward) boundaries are less clear because no microbathymetric or seafloor geodetic data are available. Hypotheses for their locations are presented. Geophysical imaging suggests that the offshore Timpe Fault System is a shallow second-order structure that likely results from extensional deformation within the moving flank. Evidence for active uplift and compression upslope of the amphitheater-shaped depression from seismic data along with subsidence of the onshore Giarre Wedge block observed in ground deformation data leads us to propose that this block is a rotational slump, which moves on top of the large-scale instability. The new shoreline-crossing structural assessment may now inform and improve kinematic models.